Answer:
xy/2
Step-by-step explanation:
use m a t h w a y
si camilo tiene 6 años mas que juan, juan tiene 7 años menos que andrés y andrés tiene 35 años
¿cuantos años tiene camilo y tiene juan? plantea la ecuación
¿cual es la diferencia entre la edad de camilo y juan?
si la abuela de andres tiene 65 años ¿la suma de las edades de camilo y juan coinciden con la edad de la abuela de andres?
Answer:
Part a) Camilo is 34 years old and Juan is 28 years old
Part b) The difference between Camilo's age and Juan's age is 6 years
Part c) The sum of the ages of Camilo and Juan not coincide with the age of Andres' grandmother
Step-by-step explanation:
The question in English is
If Camilo is 6 years older than Juan, Juan is 7 years younger than Andrés and Andrés is 35 years old .
Part a) How old is Camilo and how old is Juan? raises the equation.
Part b) What's the difference between Camilo's age and Juan's age?
Part c) If Andres's grandmother is 65 years old, does the sum of the ages of Camilo and Juan coincide with the age of Andres' grandmother?
Part a) How old is Camilo and how old is Juan? raises the equation.
Let
x -----> Camilo's age
y -----> Juan's age
z -----> Andres's age
we know that
[tex]x=y+6[/tex] -----> equation A
[tex]y=z-7[/tex] -----> equation B
[tex]z=35[/tex] -----> equation C
Find the value of y
substitute the value of z in the equation B
[tex]y=35-7=28[/tex]
Find the value of x
substitute the value of y in the equation A
[tex]x=28+6=34[/tex]
therefore
Camilo is 34 years old and Juan is 28 years old
Part b) What's the difference between Camilo's age and Juan's age?
Subtract Juan's age from Camilo's age
so
[tex]x-y=34-28=6\ years[/tex]
Part c) If Andres's grandmother is 65 years old, does the sum of the ages of Camilo and Juan coincide with the age of Andres' grandmother?
Adds Camilo's age and Juan's age
[tex]x+y=34+28=62\ years[/tex]
[tex]62\ years\neq 65\ years[/tex]
therefore
The sum of the ages of Camilo and Juan not coincide with the age of Andres' grandmother
Keith has $500 in a savings account at the beginning of the summer. He wants to have at least $200 at the end of the summer. He withdraws $25 per week for food. How many weeks can Keith withdraw money from his account?
Keith can withdraw money from his account for 12 weeks.
Step-by-step explanation:
Total savings = $500
Amount to be left in his account = $200
Withdrawal per week = $25
Let,
x be the number of weeks.
According to given statement;
Total savings - Withdrawal per week * no. of weeks = Amount to be left
[tex]500-25x=200\\-25x=200-500\\-25x=-300\\[/tex]
Dividing both sides by -25
[tex]\frac{-25x}{-25}=\frac{-300}{-25}\\x=12[/tex]
Keith can withdraw money from his account for 12 weeks.
Keywords: savings, linear expression
Learn more about linear expressions at:
brainly.com/question/4639731brainly.com/question/4655616#LearnwithBrainly
Final answer:
Keith can withdraw money from his account for food for 12 weeks before reaching his minimum account balance requirement of $200.
Explanation:
To determine how many weeks Keith can withdraw money from his account while maintaining a balance of at least $200, we need to perform a simple subtraction and division operation. First, we calculate the amount he needs to leave in the account:
$500 initial balance - $200 desired end balance = $300 available to spend.
Keith withdraws $25 per week for food. To find out how many weeks his money will last, we divide the total amount he can spend by the weekly withdrawal amount:
$300 \/ $25 per week = 12 weeks.
Therefore, Keith can withdraw money for food for 12 weeks before his account balance reaches his minimum requirement of $200.
AP:2,x,26.
Find the value of x
2,x, 26 are in A. P.
a2-a1 = a3-a2
x-2 = 26-x
2x = 26+2
2x = 28
So x = 14.
The function relating the height of an object off the ground to the time spent falling is a quadratic relationship. Travis drops a
tennis ball from the top of an office building 90 meters tall. Three seconds later, the ball lands on the ground. After 2
seconds, how far is the ball off the ground?
Answer:
the ball is on the ground after 3 seconds right so it would still be on the ground
Step-by-step explanation:
Answer:50 meters
Step-by-step explanation:
Please answer this correctly
Answer:
9:59
Step-by-step explanation:
all you have to do is add the hours to the hours and the minutes to the minutes but if you get a number over 60 in the minutes section then you need to subtract 60 from that side until get a number under 60 then you add however many times you did that to the hours
Answer:
Step-by-step explanation:
9 minutes past 4 = 04:09
Then in 5hours:50minutes, add it to 04:09, then we obtain 09:59
what value of n solves the equation 2n =1/8
A. -3
B. -4
C. 3
D. 4
Answer:
n = - 3
Step-by-step explanation:
We have to solve the equation [tex]2^{n} = \frac{1}{8}[/tex] for n.
Now, as the variable is in power, we will take a log on both sides.
So, [tex]2^{n} = \frac{1}{8}[/tex]
⇒ [tex]\log 2^{n} = \log \frac{1}{8}[/tex]
⇒ n log 2 = log 1 - log 8 {Since we know the property of logarithm [tex]\log a^{b} = b \log a[/tex] and [tex]\log \frac{a}{b} = \log a - \log b[/tex]}
⇒ n log 2 = - log 2³ { Since, log 1 = 0}
⇒ n log 2 = - 3 log 2
⇒ n = - 3 (Answer)
Find the slope of the line that goes through the given points.
(3, 5) and (3, -5)
For this case we have that by definition, the slope of a line
is given by:
[tex]m = \frac {y_ {2} -y_{1}} {x_ {2} -x_ {1}}[/tex]
Where:
[tex](x_ {1}, y_ {1})\ and\ (x_ {2}, y_ {2})[/tex] are two points through which the line passes.
According to the statement we have:
[tex](x_ {1}, y_ {1}): (3,5)\\(x_ {2}, y_ {2}): (3, -5)[/tex]
Substituting we have:
[tex]m = \frac {-5-5} {3-3}[/tex]
It is noted that the slope is undefined.
Answer:
The slope is undefined
Is (2,-5) a solution to the equation f(x)= -x - 3
Replace x in the equation with the x value of the given solution:
f(x) = -2 -3 = -5
Since replacing x with 2 , the equation equals -5, then (2,-5) is a solution.
Answer:
yes
Step-by-step explanation:
Three friends bought 4, 6, and 8 books. The table shows the cost of the books.
Number of Books 4 6 8
Cost ($) 30 45 60
What is the constant of proportionality?
(A) 2
(B) 7.5
(C) 15
(D) 30
Answer: B 7.5
Step-by-step explanation:
Y = Kx
4 = k30
k = 30/4
k = 7.5
or
Y = KX
X Y
If f(x) = 1x1 + 9 and g(x) = -6, which describes the value of (f + g)(x)?
(f + g)(x) > 3 for all values of x
(f + g)(x) < 3 for all values of x
(f + g)(x) < 6 for all values of x
(f + g)(x) 6 for all values of x
Save and Exit
Ne
Mark this and return
Answer:
The answers are "(f+g)(x)> 3 for all values of x" and "(f+g)(x)<6 for all values of x".
Step-by-step explanation:
If f(x) = 1x1 + 9 =10, then f(x) is a constant for every value of x, which means that y=f(x) will take the value of 10 no matter which value takes x.If g(x)= -6, then g(x) is a constant for every value of x, which means that it will take the value of -6 no matter the value of x.(f+g)(x)=10 + (-6) = 10 - 6= 4. Then, no matter the value of x, the function (f+g)(x) will equal 4 (a constant). According to the available options, both "(f+g)(x)>3" and "(f+g)(x)<6" are true, because (f+g)(x)=4>3 and (f+g)(x)=4 <6.Evaluate the expression. ab if a = 6 and b = 7
Answer:
42
Step-by-step explanation:
ab is a x b
[tex]a \times b[/tex]
[tex]6 \times 7 = 42[/tex]
Answer:279,936
Step-by-step explanation:
i hope its helps
Are the expressions 4b-7-
2b + 11 and b + 3+ b + 1
equivalent?
Answer:
2b+4 so yes there are equivalent
Step-by-step explanation:
4b-7-2b+11
4b-2b-7+11
2b+4
b+3+b+1
2b+4
Find m∠UVT m∠WVU = 169° m∠WVT = (2x + 20)° m∠UVT = (3x + 19)° A) 91° B) 94° C) 97° D) 100°\
Answer:
m ∠ UVT = 97° is the required answer.
Step-by-step explanation:
Given:
m∠WVU = 169°
m∠WVT = (2x + 20)°
m∠UVT = (3x + 19)°
To Find:
m∠UVT = ?
Solution:
Angle Addition Postulate is that if you place two angles side by side, then the measure of the resulting angle will be equal to the sum of the two original angle measures.
So By applying this property in the diagram below we get,
m∠ WVT + m∠UVT = m∠WVU ............{Angle Addition Postulate}
[tex](2x+20) + (3x+19) = 169\\5x + 39 = 169\\5x=169-39\\5x=130\\\therefore x=\frac{130}{5} \\\therefore x=26\\[/tex]
Now,
m∠UVT = (3x + 19)°
Substituting x = 26 we get
m∠UVT = 3 ×26 + 19
= 78 +19
∴ m∠UVT = 97°
Ten less than a number is three more than six times the number. Let n represent the number and translate each phase or sentence.
Required number is [tex]\frac{-13}{5}[/tex] and required expression is n – 10 = 6n + 3
Solution:Given that
Ten less than a number is three more than six times the number.
Number is represented by variable "n"
Need to determine equation and the number.
Ten less than number means subtracting 10 from the number
As number is n so ten less than number = n – 10 ------(1)
Six times the number = number multiplied by 6 = 6n
So three more than Six times the number = 6n + 3 --------(2)
As ten less than number is equal to 3 more than six times the number
=> n – 10 = 6n + 3
Solving the above expression for n we get
-10-3 = 6n – n
=> 5n = -13
[tex]\Rightarrow \mathrm{n}=-\frac{13}{5}[/tex]
Hence required number is [tex]-\frac{13}{5}[/tex] and required expression is n – 10 = 6n + 3
find the value of x in this figure
x equals 47 degrees
Explanation:Remember you must provide full questions in order to get excellent and precise answers. However, I have attached a figure in order to set the problem in context. Here we have a triangle. The most basic definition for a triangle is a polygon with three edges and three vertices, but there is something that is very important for all triangles:
The internal angles of every triangle add up to 180 degrees.By knowing this, we can write:
[tex]x^{\circ}+95^{\circ}+38^{\circ}=180^{\circ} \\ \\ Isolating \ x: \\ \\ x^{\circ}=180^{\circ}-95^{\circ}-38^{\circ} \\ \\ x^{\circ}=47^{\circ} \\ \\ \\ Where: \\ \\ \boxed{x=47}[/tex]
Learn more:Area of triangles: https://brainly.com/question/12051125
#LearnWithBrainly
An electrolyte solution has an average current density of 111 ampere per square decimeter \left( \dfrac{\text{A}}{\text{dm}^2}\right)(
dm
2
A
)left parenthesis, start fraction, start text, A, end text, divided by, start text, d, m, end text, squared, end fraction, right parenthesis.
What is the current density of the solution in \dfrac{\text{A}}{\text{m}^2}
m
2
A
start fraction, start text, A, end text, divided by, start text, m, end text, squared, end fraction?
Answer:
The current density of the solution in [tex]m^2[/tex] is [tex]11100A/m^2[/tex]
Step-by-step explanation:
One square decimeter is equal to 0.01 square meter, Thus the current density in square meters is
[tex]\frac{111A}{dm^2} =\frac{111A}{0.01m^2} =\frac{111}{0.01}*\frac{A}{m^2}=\boxed{11100A/m^2}[/tex]
11100 Amperes per square meter.
Answer:
The numbers are messed up, don't copy and paste from khan.
The answer is 100
Step-by-step explanation:
I took the test
11. The sum of two numbers
is 29 and the difference of the
same two numbers is 15.
What are the two numbers?
Answer:
(22, 7)
Step-by-step explanation:
Let x and y be the unknown two numbers.
x+y=29
x-y=15
----------
2x=44
x=44/2
x=22
----------
22+y=29
y=29-22=7
x=22, y=7.
From the list below, select the most likely correlation coefficient for the graphed data.
A. −0.1
B. −0.8
C. 0.8
D. 0.1
Answer:
C
Step-by-step explanation:
First of all,
if the line goes Upward (from left to right), it is sloping upward and the correlation coefficient would be POSITIVE.If the line goes Downward (from left to right), it is sloping downward and the correlation coefficient would be NEGATIVE.Since, from the graph we can see that the line is sloping upward, we know the correlation coefficient would be POSITIVE, so we can immediately eliminate choices A & B.
Now, the closer the correlation coefficient value is to 0, the less steep the line is. The closer it is to 1, the more steeper it is.
Looking at the graph, it isn't that flat, it is quite steep. So the correlation coefficient would be 0.8, NOT 0.1
So, answer choice C is right.
1. The half-life of the radioactive element krypton-91 is 10 seconds. If 32
grams of krypton - 91 are initially present, how many grams are present
after 30 seconds? Show the decay function. Use A = A0ekt
Answer:
4 g after 30 seconds.
Step-by-step explanation:
After 10 seconds 32 * 1/2 = 16 g are present.
After 20 seconds 32 * (1/2)^2 = 8 g are present
After 30 seconds 32 * (1/2)^3 = 4 g are present.
y = x - 4
-2x + y = 18
Use elimination pls
Answer:
x = -22 , y = -26
Step-by-step explanation:
Solve the following system:
{y = x - 4 | (equation 1)
y - 2 x = 18 | (equation 2)
Express the system in standard form:
{-x + y = -4 | (equation 1)
-(2 x) + y = 18 | (equation 2)
Swap equation 1 with equation 2:
{-(2 x) + y = 18 | (equation 1)
-x + y = -4 | (equation 2)
Subtract 1/2 × (equation 1) from equation 2:
{-(2 x) + y = 18 | (equation 1)
0 x+y/2 = -13 | (equation 2)
Multiply equation 2 by 2:
{-(2 x) + y = 18 | (equation 1)
0 x+y = -26 | (equation 2)
Subtract equation 2 from equation 1:
{-(2 x)+0 y = 44 | (equation 1)
0 x+y = -26 | (equation 2)
Divide equation 1 by -2:
{x+0 y = -22 | (equation 1)
0 x+y = -26 | (equation 2)
Collect results:
Answer: {x = -22 , y = -26
Answer:
x = -22, y = -26Step-by-step explanation:
[tex]\left\{\begin{array}{ccc}y=x-4&\text{subtract}\ x\ \text{from both sides}\\-2x+y=18\end{array}\right\\\\\left\{\begin{array}{ccc}-x+y=-4\\-2x+y=18&\text{change the signs}\end{array}\right\\\underline{+\left\{\begin{array}{ccc}-x+y=-4\\2x-y=-18\end{array}\right}\qquad\text{add both sides of the equations}\\.\qquad x=-22\\\\\text{Put the value of}\ x\ \text{to the first equation:}\\\\y=-22-4\\y=-26[/tex]
3x minus 7 divided by 2 equals negative 5
Answer: x=0.5
Step-by-step explanation: In order to solve this problem, you need to simplify the rest of the problem first. You can do this by dividing -7 by 2, which will result in -3.5, making the equation 3x-3.5=-5. If you add 3.5 to both sides, the equation becomes 3x = 1.5. If you divide 1.5 by 3, you are left with 0.5, so x=0.5.
Final answer:
The solution to the linear equation '3x minus 7 divided by 2 equals negative 5' is found by performing algebraic operations to isolate the variable, resulting in x = -1.
Explanation:
The question involves solving a linear equation which is a fundamental concept in mathematics. To solve the equation 3x minus 7 divided by 2 equals negative 5, you will perform algebraic operations to isolate the variable x. Here is a step-by-step process:
Multiply both sides of the equation by 2 to get rid of the denominator: 2 * (3x - 7)/2 = -5 * 2.Simplify both sides: 3x - 7 = -10.Add 7 to both sides to isolate the 3x term: 3x = -10 + 7.Simplify the right side: 3x = -3.Divide both sides by 3 to solve for x: x = -3/3.Finally, x simplifies to -1 as the solution.Applying this process, you can see that the original equation is satisfied when x = -1, which completes our solution.
". As an operator in a chemical plant, you tenda
separating machine. After you fill the tank, the
content settles for 14 hours before the liquid is
removed. You fill the tank at 1:45 A.m. When do
you remove the liquid?
A.
2:15 A.M.
B. 2:45 A.M.
C. 3:00 A.M.
D. 3:15 A.M.
E. 3:45 A.M.
Answer:
3:45 P.M.
Step-by-step explanation:
After I fill the tank, the content settles for 14 hours before the liquid is removed.
So, the liquid is removed after content settlement i.e. after 14 hours of filling up the tank.
If I fill the tank at 1:45 A.M. then after 14 hours i.e. at 3: 45 P.M I will remove the liquid.
If we separate the 14 hours into (12 hours + 2 hours), then by adding 12 hours the time will remain the same, only the A.M. will change to P.M i.e. 1: 45 P.M. and then by adding 2 hours more the time will be 3:45 P.M. (Answer)
Is 12/30 and 18/45 proportional, or not proportional?
12/30 = 18/45, so first you're going to cross multiply and you'll get (30)(18) = (12)(45). Then you can see that 540 = 540 same number so they're proportional...
BTW THIS WAY IS A LOT EASIER.
12/30 = 2/5
18/45 = 2/5
So yes, in summary, they're proportional to each other. Hope this helps, have a BLESSED and wonderful day! :-)
Answer:
proportional
Step-by-step explanation:
12/30 multiplied by a factor of 1.5 is 18/45 so it is proportional
45pts help! what is the vertex of the function
f(x)=- -|x + 7| - 4
Answer: (-7, -4)
========================================
Explanation:
The general equation y = a| x-h | + k has the vertex (h,k)
Rewrite the original function in this form to get f(x) = -1|x - (-7)| + (-4) and we see that h = -7 and k = -4
So that's why the vertex is (h,k) = (-7, -4)
The V shape graph opens downward meaning that the vertex (-7, -4) is at the highest point. The graph is shown below. I used GeoGebra to make the graph.
Answer:
-7,-4
Step-by-step explanation:
1.25×4+3×2 divided By (1/2) third power
Answer:
(1.25×4+3×2 )/((1/2)^3) = 88
Step-by-step explanation:
The solution to the equation 1.25×4+3×2 divided By (1/2) third power is 53 applying the order of operation PEMDAS.
Explanation:To solve 1.25×4+3×2 divided By (1/2) third power, we first have to follow the order of operation, that is Parentheses, Exponents, Multiplication and Division (from left to right), Addition and Subtraction (from left to right), also known as PEMDAS.
Step 1: Solve the expressions in parentheses and the exponent. As there's none, we move to the next step.
Step 2: Solve the multiplication and division.
1.25×4 equals 5, then 3×2 equals 6, and then 1/2, to the third power, equals 0.125.
So our equation now reads 5+6 divided by 0.125.
Step 3: Execute the division operation. 6 divided by 0.125 equals 48.
Our equation now reads 5 + 48.
Step 4: The last step is addition. 5 + 48 equals 53. So, the answer to the equation 1.25×4+3×2 divided By (1/2) third power is 53.
Learn more about Order of Operation here:https://brainly.com/question/15840745
#SPJ2
Anton has 1 7/8 cups of ice cream to make ice cream sundaes.He uses 2/3 cups of ice cream for each sundae.What is the maximum amount of sundaes that Anton can make with ice cream
Answer:
45/16 or 2 13/16, the maximum amount of sundaes that Anton can make with ice cream is 2.
Step-by-step explanation:
1 7/8=15/8
2/3x<=15/8
x<=(15/8)/(2/3)
x<=(15/8)(3/2)=45/16
Look at 4x + 5y - 12 - x + 3y . Have all of the like terms been combined? Explain in 1-2 sentences.
Answer:
no 4x and -x can be combined to form 3x, and 5y and 3y can be combned to form 8y. the correct equation should be 3x+8y-12
Step-by-step explanation:
What is the answer to, (4-1) . n = n . _
Answer:
(4-1)•n=n•(4-1)
Step-by-step explanation:
It should equal each other so no matter what n equals it will equal each other :3
Step-by-step explanation:
Commutative property: a · b = b · a
(4 - 1) · n = n · (4 - 1)
how many pumpkin plants would be in 2 rows
Answer:
If a vine tear is occurs after the fruit, cover it with soil and it should produce secondary roots. Number of Fruit on a Vine: A single pumpkin plant normally produces two to five pumpkins. Miniature varieties will produce up to a dozen or so.
Step-by-step explanation:
what ordered pairs are a solution to the equations
3x-5y=4
-5x+4y=2
(-7,0)
(6,8)
(3,1)
(-2,-2)
Answer:
x=-2, y=-2. (-2, -2)
Step-by-step explanation:
3x-5y=4
-5x+4y=2
-------------
5(3x-5y)=5(4)
3(-5x+4y)=3(2)
---------------------
15x-25y=20
-15x+12y=6
-------------------
-13y=26
y=26/-13
y=-2
3x-5(-2)=4
3x+10=4
3x=4-10
3x=-6
x=-6/3
x=-2
x=-2, y=-2.